Sex Differences in the Temporal Recovery of Neuromuscular Function Following Resistance Training in Resistance Trained Men and Women 18 to 35 Years - Davies, Robert W.; Carson, Brian P.; Jakeman, Philip M. (Frontiers in Physiology, 2018)
To investigate sex differences in the temporal recovery of neuromuscular function following resistance training (RT), eleven men and eight women 18 to 35 y completed a single RT bout (barbell back-squats, 80 % 1RM, 5 sets × 5 reps, 25 % duty cycle, then 1 set × max reps). Measures of muscle function (isometric, concentric, eccentric knee extensor strength, and countermovement jump (CMJ) height), serum creatine kinase activity (CK) and lower-body muscle pain were assessed before RT (0 h), +4 h, +24 h, +48 h and +72 h post-RT. Data are mean % change from PRE (SD) and effect size (ω2, d). Men and women had similar RT-experience (men, 2.1 (0.8) y vs. women 2.4 (1.0) y, P = 0.746, d = 0.3) and 1RM strength per kg lean mass (men, 1.9 (0.2) kg∙kg-1 vs. women, 1.8 (0.3) kg∙kg-1, P = 0.303, d = 0.3). A 36 (12) % increase in lower-body muscle pain was reported following RT (P < 0.05, d > 0.9). There was an absence of any overt change in CK (+24 h, 74 (41) IU•L-1; pooled mean (SD)). Decrements in knee extensor strength and CMJ height were observed +4 h to +72 h for both men and women (P < 0.05, ω2 = 0.19 to 0.69). Sex differences were apparent for of CMJ height (+24 h men, -10 (6) % vs. women, -20 (11) %, P < 0.001, d = 1.8) and isokinetic concentric strength (+24 h men, -10 (13) % vs. women -25 (14) %, P = 0.006, d = 1.8), with a more pronounced loss and prolonged recovery in women compared to men (e.g. CMJ +72 h men, -3 (6) % vs. women, -13 (12) %, P = 0.051, d = 1.1). We conclude that the different temporal recovery patterns between men and women are not explicable by differences in muscle strength, RT performance, experience, muscle damage or fatigability.